2018
DOI: 10.3390/nu10050585
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Activities of Sulforaphane and Its Metabolites in Human Hepatoma HepG2 Cells

Abstract: Sulforaphane (SFN) exhibits chemopreventive effects through various mechanisms. However, few studies have focused on the bioactivities of its metabolites. Here, three metabolites derived from SFN were studied, known as sulforaphane glutathione, sulforaphane cysteine and sulforaphane-N-acetylcysteine. Their effects on cell viability, DNA damage, tumorigenicity, cell migration and adhesion were measured in human hepatoma HepG2 cells, and their anti-angiogenetic effects were determined in a 3D co-culture model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Cells were then harvested and resuspended in PBS containing 10% DMSO. The alkaline Comet assay procedure was performed as previously described 38 . Levels of DNA strand breaks were expressed as tail intensity (% DNA in the Comet tail).…”
Section: Alkaline Comet Assaymentioning
confidence: 99%
“…Cells were then harvested and resuspended in PBS containing 10% DMSO. The alkaline Comet assay procedure was performed as previously described 38 . Levels of DNA strand breaks were expressed as tail intensity (% DNA in the Comet tail).…”
Section: Alkaline Comet Assaymentioning
confidence: 99%
“…The antiproliferative effect of the BITC metabolites agrees with previous reports on the function of the ITC metabolites. [33][34][35] The BITC-GSH conjugate showed higher cytotoxicity than BITC-NAC (Figure 2B), possibly due to the different dissociation rate of BITC; the former was more rapid than the latter (Figure 4B). The tendency of the BITC dissociation from its metabolites was quite similar to the previously reported data.…”
Section: Discussionmentioning
confidence: 99%
“…It has an inhibitory effect on cellular escalation by induction of apoptosis (Jang et al., 2015). Previous studies have also highlighted the efficacy of SFN against HepG2 cell line for in vivo studies with xenograft models (Liu, Atkinson, et al., 2017; Liu, Wang, Zhou, et al., 2018; Zou et al., 2017). Another research study concluded that SFN inhibited the proliferation, migration, and invasion of hepatocellular carcinoma cells.…”
Section: Potential Effects Of Sulforaphane Against Different Cancersmentioning
confidence: 99%